From "No Man's Land" to a "Stronger Community": Communitas as a Theoretical Framework for Successful Disaster Recovery. Issue 1 (March 2014) - Richardson, Brian K.; Siebeneck, Laura K.; Shaunfield, Sara; Kaszynski, Elizabeth
Disasters are especially threatening to small communities, which often have limited resources, personnel, and infrastructure necessary for the recovery process. Still, some small communities have demonstrated effective recovery from disasters. We wondered whether Turner's notion of communitas might serve as a useful theoretical framework for understanding effective community recovery from disaster. We interviewed 32 residents and five community leaders of a small Texas town that appeared to successfully recover from Hurricane Ike. Thematic analysis revealed the community did engage in practices that mirrored the dimensions of communitas, suggesting it is a useful framework for understanding (successful) disaster recovery. We describe implications of the study's key findings, followed by theoretical and practical implications, limitations, and directions for future research.